True myth : C.S. Lewis and Joseph Campbell on the veracity of Christianity - Menzies, James W. (Cambridge : Lutterworth Press, 2015)
True Myth examines the meaning and significance of myth as understood by C.S. Lewis and Joseph Campbell and its place in the Christian faith in a technological society. C.S. Lewis defined Christianity, and being truly human, as a relationship between the personal Creator and his creation mediated through faith in his son, Jesus. The influential writer and mythologist Joseph Campbell had a different perspective, understanding Christianity as composed of mythical themes similar to those in other religious and secular myths. While accepting certain portions of the biblical record as historical, Campbell taught the theological and miraculous aspects as symbolic--as stories in which the reader discovers what it means to be human today. In contrast, Lewis presented the theological and the miraculous in a literal way. Although Lewis understood how one could see symbolism and lessons for life in miraculous events, he believed they were more than symbolic and indeed took place in human history.
Introduction -- Myth, an attempt to define the indefinable -- C.S. Lewis and myth -- Joseph Campbell and myth -- Christianity as history, mystery, and myth -- C.S. Lewis and Joseph Campbell on the role of myth in a technological society -- Conclusion.
Online resource; title from PDF title page (EBSCO, viewed June 24, 2015)
Includes bibliographical references.
Master record variable field(s) change: 082
Keywords: Lewis, C. S. -- 1898-1963.; Campbell, Joseph, -- 1904-1987.; Campbell, Joseph, -- 1904-1987.; Lewis, C. S. -- 1898-1963.; Myth; Myth in the Bible; Christianity; BIBLES / General; RELIGION / Biblical Reference / General; RELIGION / Biblical Reference / Handbooks; Campbell, Joseph, 1904-1987.; Christianity; Lewis, C.S. (Clive Staples), 1898-1963.; Myth in the Bible; Myth; Christianity; Myth; Myth in the Bible; SOCIAL SCIENCE / Folklore & Mythology; Electronic books